Using virtual reality to analyze links between handball thrower kinematics and goalkeeper's reactions - Bideau, B.; Multon, F.; Kulpa, R.; Fradet, L.; Arnaldi, B.; Delamarche, P. (Neuroscience Letters, 2004)
This work investigates the design of a new method to evaluate the importance of visual elements taken into account by a handball goalkeeper facing a thrower. Virtual reality was used to design and reproduce standardised situations in a controlled environment. Under such conditions, it was possible to isolate for investigation one visual element in the thrower's gestures. The goalkeeper's movements were recorded in order to compare his reactions to two separate throws where only one visual element was modified. Our systems allowed us to measure and record the effects of small changes in the thrower's movements. With the numerical values we obtained from our results we were able to come up with a scale of significance for each isolated element. These preliminary results look promising for neuroscience, allowing us to better understand the strategies used in duel situations.